Ecotoxicological assessment of the anticancer drug cisplatin in the polychaete Nereis diversicolor - Fonseca, T. G. [UNESP]; Morais, M. B.; Rocha, T.; Abessa, D. M.S. [UNESP]; Aureliano, M.; Bebianno, M. J. (Elsevier, 2017)
Anticancer drugs are designed to inhibit tumor cell proliferation by interacting with DNA and altering cellular growth factors. When released into the waterbodies of municipal and hospital effluents these pharmaceutical compounds may pose a risk to non-target aquatic organisms, due to their mode of action (cytotoxic, genotoxic, mutagenic and teratogenic). The present study aimed to assess the ecotoxicological potential of the alkylating agent cisplatin (CisPt) to the polychaete Nereis diversicolor, at a range of relevant environmental concentrations (i.e. 0.1, 10 and 100 ng Pt L− 1). Behavioural impairment (burrowing kinetic impairment), ion pump effects (SR Ca2 +-ATPase), neurotoxicity (AChE activity), oxidative stress (SOD, CAT and GPXs activities), metal exposure (metallothionein-like proteins - MTLP), biotransformation (GST), oxidative damage (LPO) and genotoxicity (DNA damage), were selected as endpoints to evaluate the sublethal responses of the ragworms after 14-days of exposure in a water-sediment system. Significant burrowing impairment occurred in worms exposed to the highest CisPt concentration (100 ng Pt L− 1) along with neurotoxic effects. The activity of antioxidant enzymes (SOD, CAT) and second phase biotransformation enzyme (GST) was inhibited but such effects were compensated by MTLP induction. Furthermore, LPO levels also increased. Results showed that the mode of action of cisplatin may pose a risk to this aquatic species even at the range of ng L− 1.
Keywords: Anticancer drugs; Cisplatin; Genotoxicity; Oxidative stress; Polychaetes